Linking Corruption, Bribery, and Corporate Governance: A Country-Level Analysis - AHMED, MANSOOR; ARIF, KASHIF; ALVI, JAHANZAIB (International Journal of Psychosocial Rehabilitation, 2020)
The current study examines the impact of corruption and bribery on corporate governance compliance. The study uses panel data of 119 countries from 2010 through 2016. Data was collected from the world economic forum for GCI (Global Competitive Index) proxy of governance and CPI (Corruption Perception Index & Bribe Index) proxy for corruption and bribery. The nexus of the said variables was examined using the panel co-integration technique and vector error correction model. The findings revealed that elements of Corporate Governance: Ethical behavior of firms, Strength of Auditing and Reporting Standards, Efficacy of Corporate Boards, Protection of minority shareholder’s interest, Strength of investor Protection, Firms Accountability and independent variables such as (Irregular payments, bribes and corruption) have long-run causality to each other. These empirical outcomes revealed that there is positive causality running from corporate corruption to corporate governance. Furthermore, the Impulse response function regarding a shock to corruption has increased in 10 years with a positive influence on corporate governance factors. The appraisal of that study would keep up all countries to more yearn to perceive to intend the bribery and corruption impact on corporate governance.